Validasi Intervensi Mindful Self-Compassion (MSC) Berbasis Daring Untuk Remaja Perempuan Indonesia - Rachmanie, Aisha Sekar Lazuardini; Retnowati, Sofia (Faculty of Psychology, Universitas Surabaya, 2026)
Adolescence is a crucial stage characterized by significant developmental changes, presenting various challenges, especially for girls. These challenges are often intensified by societal pressures, heavy media consumption, and peer harassment, which can adversely affect well-being. Girls in this age group frequently face anxiety related to identity and appearance. This study evaluates an online-based Mindful Self-Compassion (MSC) program aimed at enhancing self-compassion and mindfulness among adolescent girls. The Mindful Self-Compassion (MSC) program's content validity was assessed, showing strong alignment with its objectives. Utilizing a flipped classroom model, the program combined collaborative sessions with facilitators and independent practice. A quasi-experimental research design was employed to measure the program's impact, with pretest and posttest data collected from intervention and control groups. Analysis of Covariance (ANCOVA) was conducted to control for baseline differences and assess the program's efficacy. Results indicate that the online-based Mindful Self-Compassion (MSC) program is a valid and effective tool for improving self-compassion and mindfulness, fostering positive emotions, and enhancing adaptive emotional management. Participants experienced increased self-understanding, greater acceptance of personal flaws, and the development of positive coping strategies. The findings from both analyses highlight the efficacy of the intervention in enhancing self-compassion and mindfulness among participants.